Les médias de communication audiovisuelle au service de la santé mentale - Nicolas Tilli (Communication)
The unchanging, alienating world of psychiatric institutionalization affords few occasions for patients to assert themselves as subjects and escape stigma. A groundbreaking initiative from Argentina uses communications media to provide active roles and social purpose to people with mental illnesses. Colifata is a radio station affiliated with an Argentinian psychiatric hospital where patients are the on-air hosts, establishing bridges to the outside world and giving a radically new face to mental illness. Colifata began as an underground radio before being recognized as a valuable public service and has since been copied worldwide. The author examines the station’s origins, operations, and social benefits.